Risk and protective factors for depressive symptoms and suicidality among children and adolescents in Lebanon: Results from a national survey - Evelyne Baroud; Loay Al Rojolah; Lilian A. Ghandour; Leyla Akoury Dirani; Marc Barakat; Martine El Bejjani; Wael Shamseddeen; David Brent; Fadi T. Maalouf (Journal of Affective Disorders Reports, 2020)
Background: Depressive disorders and suicidal ideations among children and adolescents present a global public health concern. Our aim is to investigate the prevalence and correlates of depressive symptoms and suicidality in a nationally representative sample of Lebanese children and adolescents. Methods: 1287 participants aged 8–17 years 11 months and their parents were recruited and completed the Mood and Feelings Questionnaire, Screen for Child Anxiety Related Emotional Disorders, Conflict Behavior Questionnaire(CBQ), Strengths and Difficulties Questionnaire, Peer Relations Questionnaire. Parents completed a sociodemographic questionnaire and the General Health Questionnaire (GHQ). Results: 79 participants (6·2%) screened positive for depressive symptoms and 147 (11·5%) had suicidal ideations. Among children, depressive symptoms were associated with suboptimal school performance (OR=11·543;95%CI=3·341–39·887), higher GHQ scores (OR=1·076;95% CI=1·045–1·108), higher odds of being victims of bullying (OR=3·545,95% CI=1·313–9·088) and of being both a victim and a bully (OR=8·700;95%CI=3·202–23·638). Suicidal ideations were associated with lower odds of having a monthly income greater than 2000$(OR=0·095;95%CI=0·012–0·760), higher odds of being victims of bullying (OR=3·392;95%CI=1·435–8·017), and of being both a victim and a bully (OR=3·347;95%CI=1·605–6·980). Among adolescents, depressive symptoms were associated with older age (OR=1·429;95%CI=1·149–1·778), school performance with some difficulties (OR=2·950;95%CI=1·408–6·181), being both a victim and a bully (OR=7·114;95%CI=2·588–19·556), higher parent reported CBQ score (OR=1·199;95%CI=1·124–1·279);. Suicidal ideations were associated with lower odds of having a monthly income between 1000 and 2000$ (OR=0·435; 95%CI=2·223–0·847), higher odds of being both a bully and a victim (OR=5·851;95%CI=2·287–14·973), higher parent reported CBQ scores (OR=1·123;95%CI=1·061–1·188). Among participants who showed depressive symptoms or suicidality, only 3.2%-14.9% had ever sought mental health care. Limitations: We couldn't comment on the progression of depressive symptoms over time or establish causality. We used a screening depression tool, not a diagnostic instrument or a suicide-specific diagnostic interview. Conclusions: Parent-child conflict, parental psychopathology and bullying emerge as correlates of depressive symptoms and suicidal ideations in children and adolescents in Lebanon and treatment gap in this population is alarming.